Phoenix: A Portable, Battery-Powered, and Environmentally Controlled Platform for Long-Distance Transportation of Live-Cell Cultures - Willbrand, Brittany N.; Loh, Sylvia; O’Connell-Rodwell, Caitlin E.; O’Connell, Dan; Ridgley, Devin M. (Frontiers in Bioengineering and Biotechnology, 2020)
Despite the advent of Advanced Therapy Medicinal Products (ATMPs) in regenerative medicine, gene therapy, cell therapies, tissue engineering and immunotherapy, the availability of treatment is limited to patients close to state-of-the-art facilities. The SCORPIO-V Division of HNu Photonics has developed the Phoenix-Live Cell Transport™, a battery-operated mobile incubator designed to facilitate long-distance transportation of living cell and tissue cultures from GMP facilities to remote areas for increased patient accessibility to ATMPs. This work demonstrates that Phoenix™ (patent pending) is a superior mechanism for transporting living cells compared to the standard method of shipping frozen cells on dry ice (-80°C) or in liquid nitrogen (-150°C), which are destructive to the biology as well as a time consuming process. Thus, Phoenix will address a significant market need within the burgeoning ATMP industry. SH-SY5Y neuroblastoma cells were cultured in a stationary Phoenix for up to five days to assess cell viability and proliferation. The results show there is no significant difference in cell proliferation (~5X growth on day 5) or viability (>90% viability on all days) when cultured in Phoenix™ and compared to a standard 5% CO2 incubator. Similarly, SH-SY5Y cells were evaluated following ground (1 to 3 days) and air (30 minutes) shipments to understand the impact of transit vibrations on the cell cultures. The results indicate that there is no significant difference in SH-SY5Y cell proliferation (~2X growth on day 3) or viability (>90% viability for all samples) when the cells are subjected to the vibrations of ground and air transportation when compared to control samples in a standard, stationary 5% CO2 incubator. Furthermore, the temperature, pressure, humidity and accelerometer sensors log data during culture shipment to ensure that the sensitive ATMPs are handled with the appropriate care during transportation. The Phoenix™ technology innovation will significantly increase the accessibility, reproducibility and quality-controlled transport of living ATMPs to benefit the widespread commercialization of ATMPs globally. These results demonstrate that Phoenix™ can transport sensitive cell lines with the same care as traditional culture techniques in a stationary CO2 incubator with higher yield, less time and labor and greater quality control than frozen samples.